27 Medical student education in sleep and its disorders: has it improved over 20 years?. (28th May 2019) - May, Felix; Romiszewski, Stephanie; Norris, Ben; Miller, Michelle; Zeman, Adam
Abstract : Objectives/Aims: There is growing recognition that sound sleep is a pillar of health, alongside adequate nutrition and exercise. Sleep problems are common and often treatable, improving lives. Twenty years ago, Stores 1 revealed the paucity of UK medical school-education on sleep disorders, with a median teaching time of 20 min: we investigate here whether this situation has changed. Methods: A cross-sectional survey of 34 medical degree courses in the UK, adapted from Stores' 1998 questionnaire, including time spent on teaching sleep medicine, sub-topics covered, and forms of assessment. Responses were coded and analysed numerically where possible; free text was analysed thematically. We excluded responses not concerned with general undergraduate education. Results: Twenty-five (74%) UK medical schools responded to our survey. The time devoted to teaching sleep medicine during undergraduate training was median 1.5 hours, mode-<1 hour, and mean 3.2 hours (standard deviation=−2.6). Only two schools reported a sleep medicine syllabus or dedicated compulsory module (8%), whilst two had optional student-selected sleep medicine modules (8%). Sleep medicine was generally described as being subsumed into other areas, primarily respiratory medicine, sometimes ENT, Psychiatry and Neurology; coverage of subtopics mirrored this pattern. Asked if enough time is allotted for teaching on sleep medicine, 50% said Yes, 38% No, 13% were unsure. Free-text comments made by our respondents had recurring themes: sleep medicine is typically subsumed into teaching by other specialties, consequently course directors are uncertain about the details of provision, obstructive sleep-apnoea is often identified as the key or only relevant sleep disorder, knowledge of sleep disorders is regarded as optional, and there is inertia about the prospect of change. However, a substantial minority of respondents are enthusiastic about making improvements to the sleep education they currently provide, and keen to use additional resources. Examples of good practice exist already, with one school offering an optional 30 hour sleep medicine module annually to 12 students. Conclusions: Little has changed since Stores' previous survey 20 years ago: sleep medicine remains a neglected topic despite agreement on the importance of sleep for general health. Sleep research is the exception rather than the rule. Obstacles to change are akin to those noted by Stores, including the views that 'sleep is not a core topic', or the 'curriculum is too crowded'. However, there is some enthusiasm for improving sleep education. Given its broad importance to health, and the existence of effective therapies, we recommend that medical schools should implement a sleep medicine curriculum. Reference: Stores, G. & Crawford, C. Medical student education in sleep and its disorders. J. R. Coll. Physicians Lond. 1998;32:149–153. Declaration of interests: Funded by the Royal Devon and Exeter Trust Research Grants Scheme. No competing interests.